(untitled) (Journal of Universal Science Research, 2025)
The article analyzes innovative methods of conducting physical culture classes. The features of innovative technologies are considered, physical education classes are used. Some traditional and non-traditional innovative methods of organizing physical culture lessons are presented. The pedagogical aspect of innovative activity and its significance in the implementation of innovative methods of conducting physical culture lessons are revealed.